2017
DOI: 10.1051/parasite/2017024
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic diseases of camels in Iran (1931–2017) – a literature review

Abstract: Parasitic diseases of camels are major causes of impaired milk and meat production, decreases in performance or even death. Some camel parasites also represent a threat to human health. About 171,500 one-humped camels (Camelus dromedarius) and 100–300 two-humped camels (Camelus bactrianus) live in Iran. Knowledge of the biodiversity of their parasites is still limited. The present review covers all information about camel parasitic diseases in Iran published as dissertations and in both Iranian and internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 77 publications
(69 reference statements)
3
69
3
Order By: Relevance
“…The vectors of Candidatus Anaplasma camelii are still bot known. Camels of Iran are mainly infested with hard ticks of the genus Hyalomma [1]. Similarly in Saudi Arabia, Tunisia and Morocco, infection of dromedaries with Anaplasma platys-like organisms occurs in dromedaries primarily infested with Hyalomma spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vectors of Candidatus Anaplasma camelii are still bot known. Camels of Iran are mainly infested with hard ticks of the genus Hyalomma [1]. Similarly in Saudi Arabia, Tunisia and Morocco, infection of dromedaries with Anaplasma platys-like organisms occurs in dromedaries primarily infested with Hyalomma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Camels are susceptible to a wide range of pathogenic microorganisms and they may act as carriers or reservoirs for several animal and zoonotic diseases [1]. However, apart from camel brucellosis and the Middle East respiratory syndrome (MERS), reports of camel-to-human transmission of zoonotic agents are either anecdotal or unsubstantiated.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the epidemiology of echinococcosis in camels in different regions of Iran is very limited (Borji & Parandeh 2010). Cross-sectional studies and parasitology tests from 1970 to 2016 showed that infected camels with E. granulosus varied from 20.73% to 70% (Afshar, Nazarian, & Baghban-Baseer, 1971;Mobedi, Madadi, & Arfaa, 1970;Moghadar, Oryan, & Pour, 1992;Mowlavi, 1997;Sazmand & Joachim, 2017) in various parts of Iran (Table 3).…”
Section: Echinococcosismentioning
confidence: 99%
“…It has been identified as the cause of numerous outbreaks of diarrhoeal disease in humans and animals all over the world (Fayer, 2004;Razavi, Oryan, Bahrami, Mohammadalipour, & Gowhari, 2009). Cryptosporidium is transmitted via the faecal-oral route and easily spreads through water, food and contact with infected animals and contaminated environments (Lal, Cornish, Fearnley, Glass, & Kirk, 2015;Sazmand & Joachim, 2017). Cryptosporidiosis is a zoonotic problem and its excreted oocysts could be the sources of human infection and great public health concern (Pieniazek et al, 2003).…”
Section: Cryptosporidiosismentioning
confidence: 99%
See 1 more Smart Citation